1001 great ideas for teaching and raising children with autism or Asperger's - Notbohm, Ellen; Zysk, Veronica (Arlington, Tex. : Future Horizons, Inc., 2010)
Contains 1001 suggestions for meeting the challenges faced by children with autism spectrum disorders, covering sensory integration, communication, language, daily living, social issues, behavior, and education.
'Previous ed. published as : 1001 great ideas for teaching and raising children with autism spectrum disorders' --T.p. verso.
Includes bibliographical references (p. 329-331) and index.
Keywords: Autistic children -- Popular works; Autism -- Popular works; Asperger's syndrome in children -- Popular works; Asperger's syndrome -- Popular works